Social Media Use Among African Youth: a Step Toward Globalization or Cultural Setback? - Ngwainmbi, Emmanuel (European Journal of Multidisciplinary Studies, 2017)
When rich countries opened up access to information and communication technology (ICT) for all types of people and countries around the world several decades ago, it was not clear to developing nations that it could transform the cultural fabric of their fragile communities and impact the economic aspirations of young people in those countries. The imbalance in cash flows between users of ICT in industrialized regions and those in poor regions, especially marginalized communities and youth cannot be compared to the general frequency of the use of, particularly social media gadgets. However, it is thought that young people aged (many 18-35) in both regions rely on social media to communicate their raw emotions (rage, love, worries and sympathies) and their political views or share data on socio-politcal and economic flaws in their national governments . In poor countries, many young people now have access to Android phones. However, it is not clear whether their use of such technology is preventing them from following their local customs or advancing the drive to compete for opportunities in the world. The study seeks to know which one of the devices was more likely to promote their understanding of and participation in the globalization process, i-phones or the internet. It examined whether the ‘internal socialization,' ‘inter—extra personal socialization’ or ‘personal advancement’ is the primary reason for ownership of the devices. Some respondents in four communities (2 cities and two rural areas) in Cameroon and S. Africa will be randomly sampled using open and close-ended questions accessible in 6 internet cafes and on the streets, and cross-analyzed. The study is expected to show a heavier use of i-phones and reliance on ‘foreign news and entertainment content’ by rural residents compared to urban populations. The study expects that results might help non-profit organizations involved with strengthening indigenous communities and foreign businesses in packaging and disseminating messages tailored for the targeted group.
Keywords: Social Media Use Among African Youth: a Step Toward Globalization or Cultural Setback